English sentence structures in Descriptive Writing: A case study of Business Management students at Indonesian vocational higher education - Beni Wijaya; Eli Yeni; Darmaliana Darmaliana; Munaja Rahma; Muhammad Nadjmuddin (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2023)
To meet the demand of current industries, the ability to write in English is highly essential in Indonesian vocational higher education. In today’s business world, students of business departments require a set of advance skills in writing business documents such as business letters and product descriptions. This research investigated the types of English sentence structures and errors in the descriptive paragraphs written by business management students of Politeknik Negeri Sriwijaya. The method used was quantitative case study research. A total of 44 descriptive paragraphs were analyzed by using syntactical structure analysis and surface taxonomy-based errors. It revealed that all types of sentence structures were used in the descriptive paragraphs. There were 34.77% simple sentence structures, 22.96% compound sentence structures, 26.36% complex sentence structures, and 15.91% compound-complex sentence structures. Thus, the most widely used was simple sentence structures. Regarding the errors, it was found that only a few errors were made by them; omission (3 errors), addition (7 errors), misformation (19 errors), and misordering (1 error). Hence, misformation was the dominant error. In summary, the students wrote their descriptive paragraphs in simple sentences mostly and made errors in misformation the most.